Vector Based Closed-Loop Control Methodology for Industrial Robots - Buschhaus, Arnd; Blank, Andreas; Franke, Jörg (ICAR 2015 - 17th International Conference on Advanced Robotics, 2015)
Improving the absolute accuracy of industrial robots is addressed by multiple activities of research institutes and robot manufacturers. Challenging in this context is an accuracy improvement of the robot during the movement. This is due to the necessity of providing time efficient and accurate target and actual state determination modules, an adequate data synchronization and a proper correction value calculation. This information can then be used to establish an online closed-loop control of the robot. One difficulty in such a system is to guarantee a smooth and steady movement despite the continuous inaccuracy compensation. To overcome this problem, recent research activities address a vector based control method. Thereby, the path planning is transferred to an external control unit, which performs all calculation steps. Based on this calculation, movement vectors synchronized with the interpolation cycle time of the robot are computed, continuously sent to the robot controller and brought to execution. These vectors include components, which describe the deviation between actual and target state and hence allow a compensation of the inaccuracies. Thereby, the robot is "pushed" along its optimal trajectory by small increments. Experiments already show good results, allowing a reactive control together with a smooth movement execution.
Keywords: Robot; Closed-Loop Control; Absolute Accuracy Improvement; Path Planning